Fatal acetaminophen poisoning with hepatic microvesicular steatosis in a child after repeated administration of therapeutic doses. (May 2020) - Bouvet, Renaud; Cauchois, Aurélie; Baert, Alain; Fromenty, Bernard; Morel, Isabelle; Turlin, Bruno; Gicquel, Thomas
Abstract: Acetaminophen is the leading cause of acute liver failure worldwide following massive ingestion. We present here a fatal acute liver failure after repeated administration of four therapeutic doses of acetaminophen at 4-h intervals in a previously healthy 9-year-old female who presented dental pain after a facial trauma during sport practice. A diagnosis of paracetamol-induced hepatitis was deduced from the clinical picture of fulminant hepatitis and tubular necrosis, the encephalopathy with oedema and without signs of trauma. Liver biopsy showed typical acetaminophen-induced necrosis and a microvesicular steatosis in periportal hepatocytes. These injuries might have been favored by pre-existing mitochondrial dysfunction related, for instance, to a deficiency in an enzyme of the mitochondrial β-oxidation pathway, or the respiratory chain. The observation of microvesicular steatosis in the periportal areas suggests an increased vulnerability via pre-existing mitochondrial dysfunction. As the liver status of patients is mostly unknown, the frequency of administration (every six hours) must be respected and the use of pharmaceutical forms allowing to adjust the dose as closely as possible to the child's weight should be promoted.